Answer:
[tex]\sf x = -\dfrac{5}{4} \qquad or \qquad -1\dfrac{1}{4}[/tex]
Step-by-step explanation:
Given expression:
[tex]\sf \dfrac{12x-3}{12} = \dfrac{12x+3}{8}[/tex]
Cross multiply:
[tex]\sf 8(12x-3)= 12(12x+3)[/tex]
Distribute inside parenthesis:
[tex]\sf 96x-24= 144x+36[/tex]
Collect like terms in one side:
[tex]\sf 96x-144x= 36+24[/tex]
Simplify following:
[tex]\sf -48x= 60[/tex]
Divide both sides by -48:
[tex]\sf \dfrac{-48x}{-48} = \dfrac{60}{-48}[/tex]
Simplify following:
[tex]\sf x = -\dfrac{5}{4} \:\ (improper\ fraction) \qquad or \qquad -1\dfrac{1}{4} \ (mixed \:\ fraction)[/tex]